2021
DOI: 10.1039/d1sc04188f
|View full text |Cite
|
Sign up to set email alerts
|

Weaving host matrices with intermolecular hydrogen bonds for high-efficiency white thermally activated delayed fluorescence

Abstract: Thermally activated delayed fluorescence (TADF) white organic light-emitting diode (WOLED) holds great promise for low-cost, large-scale lighting applications. Nevertheless, manipulating exciton allocation in a white TADF single layer is still...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 59 publications
0
2
0
Order By: Relevance
“…Furthermore, due to microcavity effect, long-wavelength component in EL spectrum of CzAcSF-hosted device was reduced, resulting in the remarkably narrowed EL profile. [22] The maximum luminance of CzAcSF : 20 % wt. cluster based diodes was beyond 6000 nits, which was 1.6 and 2 folds of host-free and BCPO hosted devices (Figures 1f and S11-S13 and Table 1).…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, due to microcavity effect, long-wavelength component in EL spectrum of CzAcSF-hosted device was reduced, resulting in the remarkably narrowed EL profile. [22] The maximum luminance of CzAcSF : 20 % wt. cluster based diodes was beyond 6000 nits, which was 1.6 and 2 folds of host-free and BCPO hosted devices (Figures 1f and S11-S13 and Table 1).…”
Section: Resultsmentioning
confidence: 99%
“…[7l,14] Therefore, "ideal" hosts in all-TADF WOLEDs should effectively suppress quenching effects, and simultaneously balance carrier flux and exciton allocation. [15] The previous reports showed that regular intermolecular hydrogen bond (IHB) networks in host matrixes can establish effective carrier transportation channels to balance carrier flux, which facilitates carrier recombination, therefore reduces excessive hole or electron induced triplet-polaron quenching (TPQ) (Figure 1A). [16] In opposite, despite weaker electrical properties, random IHBs in host matrixes can lead to disordered molecular alignment in EMLs, therefore alleviating host-dopant and dopant-dopant interaction induced triplet-triplet annihilation (TTA).…”
Section: Introductionmentioning
confidence: 99%